2017
DOI: 10.1534/genetics.117.300260
|View full text |Cite|
|
Sign up to set email alerts
|

Apico-basal Polarity Determinants Encoded by crumbs Genes Affect Ciliary Shaft Protein Composition, IFT Movement Dynamics, and Cilia Length

Abstract: One of the most obvious manifestations of polarity in epithelia is the subdivision of the cell surface by cell junctions into apical and basolateral domains. crumbs genes are among key regulators of this form of polarity. Loss of crumbs function disrupts the apical cell junction belt and crumbs overexpression expands the apical membrane size. Crumbs proteins contain a single transmembrane domain and localize to cell junction area at the apical surface of epithelia. In some tissues, they are also found in cilia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 49 publications
2
12
0
Order By: Relevance
“…At 5 dpf, homozygous crb2b e40 mutant larvae show no obvious external defects (Fig. 1B,C) and crb2b e40 mutants survive into adulthood and breed normally, as has been reported previously for a very similar allele carrying a stop codon in the Crb2b-lf signal peptide (Hazime and Malicki, 2017). Furthermore, histological analyses of tissue organisation in crb2b e40 eyes at 5 dpf did not show any apparent defect in the overall structure of the retina, the retinal pigment epithelium (RPE) or the lens (Fig.…”
Section: Introductionsupporting
confidence: 85%
See 1 more Smart Citation
“…At 5 dpf, homozygous crb2b e40 mutant larvae show no obvious external defects (Fig. 1B,C) and crb2b e40 mutants survive into adulthood and breed normally, as has been reported previously for a very similar allele carrying a stop codon in the Crb2b-lf signal peptide (Hazime and Malicki, 2017). Furthermore, histological analyses of tissue organisation in crb2b e40 eyes at 5 dpf did not show any apparent defect in the overall structure of the retina, the retinal pigment epithelium (RPE) or the lens (Fig.…”
Section: Introductionsupporting
confidence: 85%
“…Finally, we asked whether the most apical part of PRCs, the outer segment (OS), is properly formed in crb2b e40 eyes. The OS is a modified cilium, and Crb proteins are known to play a role in ciliogenesis (Fan et al, 2007;Hazime and Malicki, 2017;Omori and Malicki, 2006). Acetylated tubulin staining (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…mRNA for crb3a is strongly and almost exclusively expressed in the ear; the Crb3a protein localises to the base of hair cell kinocilia at the otic vesicle stage, and to the basal body of kinocilia in adult hair cells. Morpholino-mediated knockdown of crb3a results in shorter kinocilia in maculae (Omori and Malicki, 2006), but interestingly, in loss-of-function mutants for crb3a or crb2b, cilia in the cristae get longer (Hazime and Malicki, 2017).…”
Section: Length Control Of Cilia In the Zebrafish Ear And Lateral Linementioning
confidence: 99%
“…Short crista kinocilia were also able to develop in a strong loss-offunction kif3a mutant, which otherwise eliminates cilia in maculae of the ear and in several other tissues, including the lateral line (Pooranachandran and Malicki, 2016). Cilia length in the zebrafish ear is also governed by the activity of Crumbs genes (Hazime and Malicki, 2017;Omori and Malicki, 2006). mRNA for crb3a is strongly and almost exclusively expressed in the ear; the Crb3a protein localises to the base of hair cell kinocilia at the otic vesicle stage, and to the basal body of kinocilia in adult hair cells.…”
Section: Length Control Of Cilia In the Zebrafish Ear And Lateral Linementioning
confidence: 99%
“…This CRB2related syndrome is characterized by cystic renal disease and cerebral ventriculomegaly (Slavotinek, 2016) suggesting that ciliogenesis or ciliary functions are compromised. To support this hypothesis, it has been shown that in the zebrafish, a Crb2b isoform is essential for the elongation of the inner segment of photoreceptor (PR) and of the primary cilium of kidney cells (Hazime and Malicki, 2017;; Omori and Malicki, 2006). Finally, Crb3a and b isoforms are involved in primary ciliogenesis in MDCK cells (Fan et al, 2007;; Fan et al, 2004) while Crb3a is controlling the length of the hair cell kinocilia in the zebrafish otic vesicle (Omori and Malicki, 2006) suggesting that Crumbs proteins may play an important role in ciliogenesis.…”
Section: Introductionmentioning
confidence: 99%